2015
DOI: 10.1002/cbic.201500386
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Lipocalin‐like CghA in Decalin‐Forming Stereoselective Intramolecular [4+2] Cycloaddition

Abstract: Understanding enzymatic Diels—Alder (DA) reactions that can form complex natural product scaffold is of considerable interest. Sch 210972 1, a potential anti-HIV fungal natural product, contains a decalin core that is proposed to form via a DA reaction. We identified the gene cluster responsible for the biosynthesis of 1 and heterologously reconstituted the biosynthetic pathway in Aspergillus nidulans to characterize the enzymes involved. Most notably, deletion of cghA resulted in a loss of stereoselective dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 29 publications
3
82
0
Order By: Relevance
“…Intriguingly, the essentially same result on a homologous CghA has been reported in the biosynthesis of other tetramate decalin metabolite Sch210972 (7). 25,26 Computational analysis of the [4+2] cycloaddition with a truncated substrate indicated that the enzyme accelerates the cycloaddition a 1000-fold at 30°C. 25,26 Homologous genes are also found in the biosynthetic gene clusters of the tetramic acid-containing adducts such as equisetin (Eqx3; 90% identity) 27 and pyrrolocin (gNR600; 37%) 28 and macrocyclic adduct cytochalasin (CcsF; 27%).…”
Section: Intramolecular Daases Generating Decalin Skeletonssupporting
confidence: 51%
See 1 more Smart Citation
“…Intriguingly, the essentially same result on a homologous CghA has been reported in the biosynthesis of other tetramate decalin metabolite Sch210972 (7). 25,26 Computational analysis of the [4+2] cycloaddition with a truncated substrate indicated that the enzyme accelerates the cycloaddition a 1000-fold at 30°C. 25,26 Homologous genes are also found in the biosynthetic gene clusters of the tetramic acid-containing adducts such as equisetin (Eqx3; 90% identity) 27 and pyrrolocin (gNR600; 37%) 28 and macrocyclic adduct cytochalasin (CcsF; 27%).…”
Section: Intramolecular Daases Generating Decalin Skeletonssupporting
confidence: 51%
“…25,26 Computational analysis of the [4+2] cycloaddition with a truncated substrate indicated that the enzyme accelerates the cycloaddition a 1000-fold at 30°C. 25,26 Homologous genes are also found in the biosynthetic gene clusters of the tetramic acid-containing adducts such as equisetin (Eqx3; 90% identity) 27 and pyrrolocin (gNR600; 37%) 28 and macrocyclic adduct cytochalasin (CcsF; 27%). 29 Frequent occurrence of DAase genes with PKS-NRPS genes suggested co-evolution of these genes.…”
Section: Intramolecular Daases Generating Decalin Skeletonsmentioning
confidence: 99%
“…Biosynthesis of the acyclic substrates that contain both the dienophile and the diene are proposed to be catalyzed by the iterative functions of the highly-reducing polyketide synthases (HR-PKSs). While bioinformatic analysis and genetic evidences have suggested a class of lipocalin-like enzymes may be involved in the formation of the decalin ring systems of Sch210972 12 and equisetin, 13 no direct biochemical evidence of enzyme-catalyzed IMDA reaction has been described. This is in part due to the inability to capture an acyclic substrate required for activity verification.…”
mentioning
confidence: 99%
“…Immediately adjacent is mycB encoding a potential DAase that has sequence homology (36% identity) to CghA, which has been implicated to be involved in the cycloaddition during Sch210972 biosynthesis. 12 A trans -acting enoylreductase (ER) is encoded in mycC (Figure 2A). This three-gene cassette is found widely among sequenced fungi (Figure S10).…”
mentioning
confidence: 99%
“…Enzymes known to catalyze intramolecular Diels-Alder reactions have been identified. [64][65][66][67][68][69] Interestingly, the enzyme TedJ shows homology to previously identified Diels-Alderases, 70 suggesting that this protein may be responsible for formation of the decalin ring.…”
Section: Biosynthesismentioning
confidence: 99%